Determination of intestinal parasites in owned dogs from the city of Talca, Chile, and its association to epidemiological variables - Muñoz-Caro, Tamara (2023)
The presence of potentially zoonotic intestinal parasites was determined from the faeces of dogs with owner in the city of Talca, Chile, through convenience sampling (n=100) between July and December 2020. The samples were analysed using the modified technique of diphasic sedimentation with formol-diethyl ether. An 18% prevalence of samples positive for intestinal parasites was found. Two species were identified: Toxocara canis (14%) and Trichuris vulpis (5%), both with zoonotic potential. In addition, three epidemiological variables were evaluated: age, confinement and health status using the Chi-square tests, Fisher's exact test and Odds ratio, finding statistical significance for the variables age (p<0.05) and confinement (p=0.001). Given that sampled dogs have owner, the results show the importance of responsible pet ownership, correct deworming, and the role of veterinarians in educating the population regarding the importance of animal health care and the associated risks of transmission of zoonotic parasites from pets to humans.